2022
DOI: 10.31635/ccschem.021.202101297
|View full text |Cite
|
Sign up to set email alerts
|

Light-Driven Ion Transport in Nanofluidic Devices: Photochemical, Photoelectric, and Photothermal Effects

Abstract: Light-driven ion transport in nanofluidic devices is a phenomenon where ions move unidirectionally by consuming optical energy, either from low concentration to high concentration or vice versa. The unidirectional ion transport driven by light offers intriguing application potential in desalination and ions separation, osmosis energy harvesting, and ionic machines benefiting from the remote noncontact light stimulus. Here, we review recent progress in nanofluidic-based light-driven ion transport systems and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…[ 96 , 97 , 98 , 99 , 100 ] Furthermore, nanofluidic‐based, light‐driven ion‐transport systems can work based on three different underlying working principles, i.e., photochemical, photoelectric, and photothermal effects, by creating an asymmetric surface charge distribution. [ 101 ] For example, some semiconductor nanostructures can realize the ion‐pumping function directly via ion transport coupled by photoinduced carriers. Xiao et al.…”
Section: Artificial Nanoionicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 96 , 97 , 98 , 99 , 100 ] Furthermore, nanofluidic‐based, light‐driven ion‐transport systems can work based on three different underlying working principles, i.e., photochemical, photoelectric, and photothermal effects, by creating an asymmetric surface charge distribution. [ 101 ] For example, some semiconductor nanostructures can realize the ion‐pumping function directly via ion transport coupled by photoinduced carriers. Xiao et al.…”
Section: Artificial Nanoionicsmentioning
confidence: 99%
“…[96][97][98][99][100] Furthermore, nanofluidicbased, light-driven ion-transport systems can work based on three different underlying working principles, i.e., photochemical, photoelectric, and photothermal effects, by creating an asymmetric surface charge distribution. [101] For example, some semiconductor nanostructures can realize the ion-pumping function directly via ion transport coupled by photoinduced carriers. Xiao et al [80] reported a carbon nitride nanotube membrane that can achieve pumped ion transport against a 5000 concentration gradient by creating a gradient surface charge density with light illumination.…”
Section: Ion Transport Phenomenon In Large Pore Size (2-100 Nm)mentioning
confidence: 99%
“…The consequent asymmetric charge distribution along the nanochannel generates a potential gradient that drives charged ion transport against their concentration gradient. This photoelectric effect only occurs when the bandgap of photoinduced carriers is insufficient to split water (1.23 V) or drive the chemical reaction, and the reversed ion transport highly depends on the directional carriers’ movement . On the basis of this mechanism, Xiao et al reported a light-driven ion pump made from carbon nitride nanotube (CNN) with an inner diameter of ∼30 nm (Figure d).…”
Section: Light-driven Ion Pumpsmentioning
confidence: 99%
“…This photoelectric effect only occurs when the bandgap of photoinduced carriers is insufficient to split water (1.23 V) or drive the chemical reaction, and the reversed ion transport highly depends on the directional carriers' movement. 72 On the basis of this mechanism, Xiao et al 73 reported a light-driven ion pump made from carbon nitride nanotube (CNN) with an inner diameter of ∼30 nm (Figure 5d). Because of the light-induced separation of electrons and holes in the CNN, the surface charge would be redistributed under the illumination.…”
Section: Light-driven Ion Pumpsmentioning
confidence: 99%
“…With the rapid development of nanotechnology, various functional solid‐state nanofluidic devices responding to diverse external stimuli including physical and chemical ones such as light, [65–67] temperature, [68,69] voltage, [70,71] magnetism, [72] pH, [73,74] ions [75] and molecules, [76] have been fabricated with different kinds of materials to selectively regulate mass transport [14] . In particular, the photo‐responsive solid‐state nanopores/nanochannels have attracted a wide range of attention from multidisciplinary fields due to their unique superiority over other external stimuli.…”
Section: Introductionmentioning
confidence: 99%